Morphology Transformation Pathway of Block Copolymer‐Directed Cooperative Self‐Assembly of ZnO Hybrid Films Monitored In Situ during Slot‐Die Coating. (12th August 2021) - Tian, Ting; Yin, Shanshan; Tu, Suo; Weindl, Christian L.; Wienhold, Kerstin S.; Liang, Suzhe; Schwartzkopf, Matthias; Roth, Stephan V.; Müller‐Buschbaum, Peter
Abstract: Cooperative self‐assembly (co‐assembly) of diblock copolymers (DBCs) and inorganic precursors that takes inspiration from the rich phase separation behavior of DBCs can enable the realization of a broad spectrum of functional nanostructures with the desired sizes. In a DBC assisted sol–gel chemistry approach with polystyrene‐ block ‐poly(ethylene oxide) and ZnO, hybrid films are formed with slot‐die coating. Pure DBC films are printed as control. In situ grazing‐incidence small‐angle X‐ray scattering measurements are performed to investigate the self‐assembly and co‐assembly process during the film formation. Combining complementary ex situ characterizations, several distinct regimes are differentiated to describe the morphological transformations from the initially solvent‐dispersed to the ultimately solidified films. The comparison of the assembly pathway evidences that the key step in the establishment of the pure DBC film is the coalescence of spherical micelles toward cylindrical domains. Due to the presence of the phase‐selective precursor, the formation of cylindrical aggregates in the solution is crucial for the structural development of the hybrid film. The pre‐existing cylinders in the ink impede the domain growth of the hybrid film during the subsequent drying process. The precursor reduces the degree of order, prevents crystallization of the PEO block, and introduces additional length scales in the hybrid films. Abstract : The complex film formation process during slot‐die coating of polystyrene‐ block ‐poly(ethylene oxide)/ZnO hybrid films is investigated with in situ X‐ray scattering. Both, cooperative self‐assembly and self‐assembly pathways during solution‐to‐film transition involve multistep structural transformations triggered by solvent evaporation.